2010
DOI: 10.1007/s10964-010-9516-7
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Conflict Resolution Styles in Parent–Adolescent Relationships: A Four-Wave Longitudinal Study

Abstract: In this study, changes in three conflict resolution styles in parent–adolescent relationships were investigated: positive problem solving, conflict engagement, and withdrawal. Questionnaires about these conflict resolution styles were completed by 314 early adolescents (M = 13.3 years; 50.6% girls) and both parents for four consecutive years. Adolescents’ reported use of positive problem solving increased with mothers, but did not change with fathers. Fathers reported an increase of positive problem solving wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
74
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 33 publications
4
74
1
4
Order By: Relevance
“…The results showed the correlation at significant level of 0.01 in total scores of 0.31 and 0.39 for conflict frequency and intensity (12). Validity of Robin and Foster research (1989) which showed the ability of conflict behavior questionnaire in splitting the families with and without clinical problems, supported the differential validity of this tool (6).…”
Section: Parents' Conflict Behavior Questionnaire Parents Formmentioning
confidence: 81%
See 2 more Smart Citations
“…The results showed the correlation at significant level of 0.01 in total scores of 0.31 and 0.39 for conflict frequency and intensity (12). Validity of Robin and Foster research (1989) which showed the ability of conflict behavior questionnaire in splitting the families with and without clinical problems, supported the differential validity of this tool (6).…”
Section: Parents' Conflict Behavior Questionnaire Parents Formmentioning
confidence: 81%
“…This scale is graded based on Likert scale and the individuals' score is graded as conflict intensity average in conflicted subject from 0 (Calm) to 5 (angry). Conflict behavior questionnaire is for teenager's parents and the higher score shows more conflict between teenager and parents (6).…”
Section: Parents' Conflict Behavior Questionnaire Parents Formmentioning
confidence: 99%
See 1 more Smart Citation
“…These patterns usually start at adolescence and continue into adulthood (3). Changes during adolescence, such as an increasing sense of independence and autonomy (4) and accelerating rate of growth, are some of the risk factors related to the development of inappropriate food patterns and consequently overweight and obesity (5).…”
Section: Introductionmentioning
confidence: 99%
“…Negative family characteristics include poverty, separation, and child abuse in contrast to protective qualities such as living in a small, nuclear family and support from extended family. A mother-daughter study found that daughters copied the coping styles of their mothers; but, despite Frydenberg's claim of causality, it would have benefitted her to conduct such an experiment across all parent-child relationships instead of mother-daughter exclusively, such as those between mother and son or father and son, given that we know that there may be important differences in how adolescents resolve conflict with parents (see Van Doorn et al 2011). It also would have been important given the significance of gender differences in factors contributing to positive youth development (see O'Connor et al 2011;Rueger et al 2010).…”
mentioning
confidence: 99%